2012
DOI: 10.1371/journal.pone.0050551
|View full text |Cite
|
Sign up to set email alerts
|

High Isoniazid Resistance Rates in Rifampicin Susceptible Mycobacterium tuberculosis Pulmonary Isolates from Pakistan

Abstract: BackgroundRapid new diagnostic methods (including Xpert MTB/RIF assay) use rifampicin resistance as a surrogate marker for multidrug resistant tuberculosis. Patients infected with rifampicin susceptible strains are prescribed first line anti-tuberculosis therapy. The roll out of such methods raises a concern that strains with resistance to other first line anti-tuberculosis drugs including isoniazid will be missed and inappropriate treatment given. To evaluate implications of using such methods review of resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
2
3
2
1
Order By: Relevance
“…Our results show a prevalence higher than what has been reported in Pakistan, 2.2%[27]; Chile, 2.2%; [28] Madagascar, 3.6%; [29] Taiwan, 5.1%; [8] Denmark, 3.6%; [30] Iran, 6.1%;[31] Israel, 6.4%;[32] Ethiopia, 7.4%; [33] Peru 8.2%;[34] and lower to reports from a tertiary hospital in Taiwan 10.9%. [35] Compared to global estimates, the prevalence of IMR in our study was similar to the upper level of the world estimate of 0.0 to 9.5%.…”
Section: Discussioncontrasting
confidence: 81%
“…Our results show a prevalence higher than what has been reported in Pakistan, 2.2%[27]; Chile, 2.2%; [28] Madagascar, 3.6%; [29] Taiwan, 5.1%; [8] Denmark, 3.6%; [30] Iran, 6.1%;[31] Israel, 6.4%;[32] Ethiopia, 7.4%; [33] Peru 8.2%;[34] and lower to reports from a tertiary hospital in Taiwan 10.9%. [35] Compared to global estimates, the prevalence of IMR in our study was similar to the upper level of the world estimate of 0.0 to 9.5%.…”
Section: Discussioncontrasting
confidence: 81%
“…In a study by Fasih et al in 2009-2011 on 7738 M. tuberculosis lung specimens in Pakistan, cultured in the Löwenstein-Jensen medium, it was found that the concurrent resistance to isoniazid, pyrazinamide, and ethambutol was 1%, while resistance to isoniazid, pyrazinamide, ethambutol, and streptomycin was 1.7%. 10 The results of this study are similar to those of the current study, in which it was also found that co-levels of isoniazid and rifampin were 2%. In a study carried out by Tavanai Sani et al in 2012, 125 samples of positive TB in Mashhad were cultured and antibiogrammed.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, 60–80% of INH resistance is due to a single mutation (S315T) in the katG gene at codon 315 [ 29 – 34 ], with the rest occurring in other genes, such as in the promoter region of inhA and in ahpC genes [ 35 37 ]. INH resistance, however, is not commonly used as an independent marker for MDR-TB [ 38 42 ]. From the compiled data, the target mutation sites selected for MDR-TB determination in this study are rpoB codons 531, 526 and 516 for the rpoB assay in the determination of RIF resistance, with one mutation type of interest for codon 531 (L), four for codon 526 (Y, R, D and L), and one for codon 516 (V) ( Table 1 ), with the highest statistical prevalence worldwide [ 17 , 18 , 23 28 , 43 47 ].…”
Section: Resultsmentioning
confidence: 99%